Pola Makan dan Obesitas Sentral pada Pasien Penderita Diabetes Melitus Tipe 2 di RSUD Tora Belo Kabupaten Sigi, Provinsi Sulawesi Tengah - Catherine Natawirarindry; Stevi Stevi; R.L.N.K Retno Triandhini (Jurnal Keperawatan Muhammadiyah, 2022)
Background:  Diabetes Mellitus is a disease that is a health problem in Indonesia and even in the world. From year to year, people with Diabetes Mellitus continue to experience a significant increase. Factors that trigger the development of diabetes mellitus are irregular eating patterns, heredity, obesity, lifestyle, lack of exercise, pancreatic infection disease and gestational pregnancy. Associated with the factors causing Diabetes Mellitus, central/abnormal obesity is the main cause of type 2 diabetes mellitus. Middle. The method used in this research is descriptive quantitative with data collection instruments in the form of SQ-FFQ and food recall 3x24 hours. The sample in this study amounted to 43 respondents who were all outpatients who came in February-April 2021 who met the inclusion criteria. This study uses a demographic data instrument and then processed using Microsoft Excel software and the results of the data obtained are displayed in tabular form. The results showed that 76.74% of respondents had a BMI which was in the obese category and all respondents had a RLPP above normal (100%) and a low-fiber diet that was below 400-600 grams/day and a high level of carbohydrate intake (48.83%) thus causing uncontrolled sugar levels. Most of the respondents had high blood pressure, both systolic and diastolic.